ARTIFICIAL INTELLIGENCE AND ACCESS TO JUSTICE: A SYSTEMATIC REVIEW OF THE INTERNATIONAL LITERATURE - Melo Júnior, José Eustáquio; Rodrigues, Waldecy (Seven Editora, 2025)
The text discusses the relationships between the use of artificial intelligence (AI) in the Judiciary and access to justice, highlighting the lack of in-depth studies on the subject. Relevant investigations and systematic reviews of the literature are identified, showing the urgency of understanding the impacts of AI on justice. The research seeks to explore the gains and risks of this use, questioning whether it can make justice more unfair. DOI: https://doi.org/10.56238/sevened2024.037-194